Problematising the South African Higher Education inequalities exposed during the Covid-19 pandemic: Students’ perspectives - Knowles, Corinne; James, Abongile; Khoza, Lebogang; Mtwa, Zikhona; Roboji, Milisa; Shivambu, Matimu (Critical Studies in Teaching and Learning, 2023)
Former Rhodes University students, co-authors of this article, were engaged in a knowledge-making project during the Covid-19 pandemic. This paper is a product of that project, where participants deliberated on the inequalities in the education sector based on their experiences in their university. These were exposed and exacerbated by the pandemic. Using a decolonial theoretical lens, they present the experiences of students to critique university decisions at the time. They argue for a reconnection with the idea of the university as a public good, as an antidote to the neoliberal tendencies that perpetuate inequality in the sector. This requires a reconnection with its own students, and to collaborate with them to find strategies to deal with crises such as the Covid-19 pandemic. Additionally, a reconnection between the university and the school sector could lead to greater synergy and an easier transition between school and university.